Macroeconomic performance of the Czech Republic during the global pandemic crisis - Volejníková, Jolana; Kuba, Ondřej (EDP Sciences - Web of Conferences, 2021)
Research background: The global SARS-CoV-2 pandemic is unprecedented for human society. Despite the continuing uncertainty about the future, it is certain that the global consequences of the pandemic will have many dimensions. Among others, the economic impacts are extremely significant. However, the sudden slowdown in economic activity, the declared quarantines, and the state of emergency have many specific impacts in individual countries. The Czech economy (as well as other countries in the world) was exposed to an unexpected exogenous shock. The data confirm that, in 2020, the decline in the performance of the Czech economy was the deepest in its history. Purpose of the article: The primary goal of this article is to analyze the macroeconomic performance of the Czech Republic during a pandemic crisis. However, we also research the impact of the pandemic on individual sectors of the national economy in the context of government measures. Methods: The analytical part of the article is processed on the basis of publicly available statistical data, economic analyses, and economic forecasts of renowned institutions. The derivation and argumentation of the conclusions are based on an empiric-inductive approach, methods of synthesis, and comparison. Findings and value added: The article maps the direct and mediated macroeconomic effects of the pandemic crisis in the reality of the Czech Republic. At the theoretical level, the aim of the article is to bring new knowledge to current economic theory, especially in the field of macroeconomics and sectoral analysis as well as the theory of public choice.
Makroekonomická výkonnost České republiky během globální pandemické krize
Keywords: globalization; SARS-CoV-2; macroeconomics; government action; Czech Republic; globalizace; SARS-CoV-2; makroekonomika; opatření vlády; Česká republika